The dynamics of operation in the regional development in Algeria: Field study - Wilaya of Souk-Ahras - BERROUK, TAREK BRIK (Journal of Humanities & Social Sciences, 2019)
This study dealt with an important topic and an important file that attract the attention of many researchers in many fields, such as economics, politeness and sociology, namely the subject of operation and specifically the dynamics of operation in the regional development in Algeria, through which we tried to customize the most important devices and programs of operation approved by the State, and revealed the extent of their contribution in advancing the development in the territory of the Wilaya (province) of Souk-Ahras. The high rate of unemployment, making the state think of alternative programs contributed to the absorption of human resources are working to be a pillar of development, especially if it is organized and invested and exploit the energies of the best exploitation. This study is a subsequent study of a previous study (the role of youth employment programs in the promotion of work and development of competencies) in this field (operating), which is the starting point for subsequent study later (the phenomenon of invasion of the female component of the labor market, professional integration, professional conscience - values ​​and ethics) , The subject has been addressed in all its possible and available aspects, in accordance with a systematic plan that reinforces our field vision to build this study, based on a central question: What is the reality of operationalization in the development of the territory of the Wilaya (province)? The study found a major outcome: * The ineffectiveness and effectiveness of the strategy and programs of employment at the national and local level in advancing development because of adopting the problems of young people and removing them from unemployment temporarily. Based on this, we had to make a set of recommendations that would contribute to providing an appropriate aspect of the workforce, whether qualified or ineligible: In order for the employment sector to participate in the development process, the government must have a genuine and serious desire to create permanent jobs in all sectors without exception. * Encourage employment development by proposing measures that allow the supply of demand to be rounded up in this operating area.